Perencanaan Pembangunan WAN Menggunakan EIGRP Dynamic Routing - Slamet Riyadi; Ade Surya Budiman (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
The development of company's business area will have implications for the development of computer network infrastructure as a means of exchanging data and information between regions. As a company that continues to develop its business area, PT. Timur Raya Lestari requires a computer network infrastructure that is adaptive to the development of the number of branch offices. The company's computer network currently uses the Static Routing method in determining the interconnection path between Routers connecting the head office and branch offices. The development of a dynamic company must be accompanied by the development of a dynamic network infrastructure as well. Development of a network infrastructure that continues to develop requires Dynamic Routing Protocol. In this study, it was simulated the use of EIGRP as Dynamic Routing Protocol for PT. Timur Raya Lestari. From the simulation results using Cisco Packet Tracer software, it can be seen that there is a stable interconnection, both for existing networks plan and planning for adding networks on new branch offices.